THE PROBLEM OF YOUTH USE MUSICAL SUBCULTURE IN THE SPIRITUAL EDUCATION OF SENIOR STUDENTS (Pedagogy of Higher and Secondary Education, 2004)
It was considered the insertion of various educational forms in out-of-school activities based on the principle of unity of pedagogical management with the development of pupil's activity, self-dependence, and initiative as one of pedagogical conditions used in spiritual senior pupils’ education of youth musical subculture.